The Emerging Regulation of VEGFR-2 in Triple-Negative Breast Cancer - Zhu, Xiaoxia; Zhou, Wen (Frontiers in Endocrinology, 2015)
Vascular endothelial growth factor-A (VEGF) signals vascular development and angiogenesis mainly by binding to VEGF receptor family member 2 (VEGFR-2). Adaptor proteins mediate many VEGFR-2’s functions in the development of blood vessels. Cancer cells secrete VEGF to activate VEGFR-2 pathway in their neighboring endothelial cells in the process of cancer-related angiogenesis. Interestingly, activation of VEGFR-2 signaling is found in breast cancer cells, but its role and regulation are not clear. We highlighted research advances of VEGFR-2, with a focus on VEGFR-2’s regulation by mutant p53 in breast cancer. In addition, we reviewed recent FDA-approved tyrosine kinase inhibitor drugs that can inhibit the function of VEGFR-2. Ongoing preclinical and clinical studies might prove that pharmaceutically targeting VEGFR-2 could be an effective therapeutic strategy in treating triple negative breast cancer.